TEACHING SPEAKING ABILITY THROUGH ROLE PLAY - (F12207032), Sunardi; Arifin, Zainal; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The purpose of this research is to know whether role play can increase the students ability in speaking of the tenth grade of second semesters students of SMA Negeri 1 Pesaguan Ketapang in academic year 2011/2012. A pre-test was given to the students, and then the application of using role play was carried out as the treatment. After the treatment, the students were tested (post-test). The interval score of post-test and pre-test is 11.47. Based on the formulation of the effect size analysis (0.07), it can be concluded that teaching speaking ability through role play can increase the students speaking ability. Keyword: teaching, speaking ability, and role play